Prevalence of scabies and associated factors among school age children in Qoloji IDP in Babile district, Somali, Eastern Ethiopia - Ahmed Mohammed Ibrahim; Abebe Belay Reta; Mohyadin Abdullahi Ahmed; Ramadan Budul Yusuf; Abdilahi Ibrahim Muse; Mohamed Omar Osman; Seid Muhumed Abdilaahi; Mustafe Abdi Ali; Kadar Ahmed Bile (PLoS ONE, 2025)
Background Scabies is a contagious ectoparasite of the skin. It is caused by the mite Sarcoptes scabiei var. Scabies occurs worldwide among people of all ages, races, genders and social classes and has been identified as a neglected tropical infectious disease. In Ethiopia, there is currently social unrest, conflict, and human-made disasters, leading to the displacement of the population from one place to another. Scabies is one of the most common skin diseases among the internally displaced population, where hygiene and sanitation are poor. The aim of the study was to assess prevalence of scabies and associated factors among school age children in Qoloji IDP in Babile District, Somali, Eastern Ethiopia. Methods A cross-sectional community-based study design was carried out in 422 among school aged children from June to July 2022. The data was collected by using observation (clinical investigation), structured questionnaires. Data was coded, entered and cleaned using with epi data version 3.1, and exported and analysis was done by using SPSS statistical software package version 22. Logistic regression analysis was used to identify factors associated with scabies. Findings were presented by using 95% CI of Crude Odds Ratios (COR) and Adjusted Odds Ratios (AOR). To declare statistical significance, a p-value of less than 0.05 was used. Results There were 63 cases of scabies with a prevalence of 14.92% CI at 95% (11.7%-18.1%). The multivariable logistic regression shows that age categories with 5-9 [AOR = 2.4 (95% CI: 1.01,6.39)], over-crowding index greater than 1.5 [AOR = 10 (95% CI: (3.6,27.8)] washing clothes infrequently [AOR =  14.7(95% CI: 3.6,25)), history of contact with scabies patients in the past 2 months [AOR =  5(95% CI: (1.2,23.0)], and Family having rash in the past two weeks [AOR = 9.9 (95% CI: 3.7,26)] having poor knowledge about scabies among children’s family [AOR = 8.9 (95% CI: 3.3,24)] were significant variables at p-value less than 0.05. Conclusion There was a higher prevalence of scabies in the study area. Age, overcrowding, washing clothes infrequently, history of contact with scabies patients in the past 2 months, family having a rash in the past two weeks, and poor knowledge about scabies among children’s families were significant factors. Health education on personal hygiene, avoiding sharing clothes with others, avoiding contact, sleeping with scabies-ill people, and sharing beds with others are important measures in reducing these risk factors.